Photocatalytic Degradation of Rhodamine-B on Synthesized Nano-Hybrid CdS Catalyst - Wang, Yin; Xu, Ling; Wang, Yuelin; Liu, Zongrui (Asian Journal of Chemistry, 2015)
In this paper, CdS/SBA-15 nano-hybrids are prepared by in situ synthesis method with the assistance of silane coupling agent. The catalyst was characterized using of XRD, FT-IR, TEM and N2 adsorption-desorption. It was found that the CdS nanocrystals were confined in the channel of SBA-15. In addition, the prepared catalyst was used to photodegrade the rhodamine-B. Different catalytic conditions were investigated, the best degradation rate could reach 95 %.